PENINGKATAN KUALITAS KARYA TULIS ILMIAH MAHASISWA MELALUI PELATIHAN MANAJEMEN REFERENSI BERBASIS MENDELEY - Helmi, Dewilna; Asep, Asep; Ansiska, Paisal (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2022)
The training to improve the quality of scientific writing through the delay-based reference management is part of the community service developed by the author. Community service is part of the implementation of the higher education tridharma that must be carried out by lecturers. Mendeley is presented to students as a form of response to the formation of a reference culture quickly, precisely and regularly. This service activity in a certain period of time in the future is expected to provide benefits to students themselves, both in terms of completing lecture assignments or long-term completion of final assignments. This training activity provides an output in the form of a community service journal that describes the response and satisfaction of students in understanding the delay application. Data related to satisfaction itself were collected and described in a qualitative descriptive manner